2017
DOI: 10.5430/ijfr.v9n1p189
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Unsystematic Risk on Stock Returns in an Emerging Capital Markets (ECM’s) Country: An Empirical Study

Abstract: In this study, we aim to introduce behavior of unsystemayic risk and its forecasting ability in prediction of future return in Egyptian Stock Exchange (ESE) as an Emerging Capital market (ECM), over the period of 2006 to 2015. We measure equally weighted unsystemayic volatility by following the Campbell's (2001) Indirect Method, by considering market size and weekly basis. Our results reveal that unsystemayic risk is the biggest component of total volatility and show no trend, although market volatility has a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…A study by Grinblatt and Titman (1989) also document that only systematic risk is important to holders of diversified portfolios. The irrelevance of idiosyncratic risk is further supported in a recent study by Masry & Menshawy (2018) who show that unsystematic risk measured by individual share price volatility is not a significant predictor of Egyptian stock market returns over the period 2006 to 2015. In contrast some studies show that for incompletely diversified funds, idiosyncratic may still influence returns (Moreno & Rodrıguez, 2013;Kinnunen & Martikainen, 2017).…”
Section: Introductionmentioning
confidence: 74%
See 1 more Smart Citation
“…A study by Grinblatt and Titman (1989) also document that only systematic risk is important to holders of diversified portfolios. The irrelevance of idiosyncratic risk is further supported in a recent study by Masry & Menshawy (2018) who show that unsystematic risk measured by individual share price volatility is not a significant predictor of Egyptian stock market returns over the period 2006 to 2015. In contrast some studies show that for incompletely diversified funds, idiosyncratic may still influence returns (Moreno & Rodrıguez, 2013;Kinnunen & Martikainen, 2017).…”
Section: Introductionmentioning
confidence: 74%
“…However their returns are also more uncertain due to political instability, exchange controls or if restrictions in repatriation of funds are imposed by that country. As a result of these uncertainties, their shares prices tend to be more volatile compared to mature economies (Masry & Menshawy, 2018). Prior studies have also shown that fund managers can influence the market risk exposure of the fund.…”
Section: Idiosyncratic Risk As a Moderating Variablementioning
confidence: 99%
“…A robustness check in this study will examine the link between daily returns on Bitcoin and signals generated by the trading rules used (hypothesis H3). TA assumes that investors follow signals emitted at time t − 1, and that trades are executed at time t. That is, the demand (supply) of any particular security will exceed supply (demand) at time t, which will cause the price to either increase, thereby activating buy signals, or decrease to trigger sell signals at time t: The momentum effect is backed by one of the basic beliefs in TA, where the market is said to discount all types of information like fundamentals, non-fundamentals and even rumours (Masry, 2018). Since the early 1990s, the only other paper that has attempted to study the relationship between returns and signals is that of Bessembinder and Chan (1995) which applied a similar framework as in Eqn (9):…”
Section: Consistency and Robustness Checkmentioning
confidence: 99%
“…The capital structure of ECM companies is generally characterised by a significant low share of long-term debt, and because of the underdeveloped bond market, banks are the main source of debt financing in general. This implies that ECM companies are subject to more financial restrictions (Masry and Heba, 2018). Fazzari et al (1988) showed that companies with larger financing constraints retain the majority of their income.…”
Section: Financial Riskmentioning
confidence: 99%
“…They are often of more recent origin, have less information efficiency, and are smaller and more volatile. ECMs also differ from these developed markets due to other characteristics, such as corporate governance, taxation of capital gains, unsystematic risk and dividends, and ownership structure (Masry and Heba, 2018). In addition, ECMs, including Egypt, are typically characterised by a concentration of ownership and financial systems that are more bank-oriented than market-oriented.…”
Section: Introductionmentioning
confidence: 99%